PANCASILA AND THE DEVELOPMENT OF DEMOCRACY IN INDONESIA: AN AXIOLOGICAL PERSPECTIVE - Wahyudin Wahyudin; Koento Wibisono Siswomiharjo; Kaelan Kaelan (Universitas Gadjah Mada, 2019)
Pancasila, as the most powerful ideology, should be implemented by the nation leader in all spheres of life, according to life philosophy “ing ngarsa sung tuladha, Ing madya mangun karsa, Tut wuri handayani”, should be integrated in all aspects of democratic lives in Indonesia. If doing so, the society will have the mental protection of all Indonesian, all of Indonesia’s bloodshed securely, in accordance with the objectives of the Indonesian state, united, sovereign, fair, and prosperous. But in its context, Pancasila is faced with problems such as the democracy that does not prioritize aspirations to actualize social justice and prosperity, the existence of an undirected democracy, the less and lower level of public trust in the government, the loss of noble values because everything is measured by money, and an indecisive government system that led to anarchy and radicalism. The method used in this study was descriptive qualitative philosophical, describing the data consisting of arguments and contextual events. This study focused on actual problems by understanding phenomena holistically about the concept of Pancasila as the basis and direction of democracy. This study used axiology theory; the material value that is useful for human physical life and spiritual values. The results of the study showed that the ideology of Pancasila should be the foundation of society life, nation and state of Indonesia because Pancasila is still and always relevant to protect the nation’s security from radicalism, liberalism, and anarchism. As a result, the goal of Pancasila as ideology is to create fair freedom in the life of the nation.